Original paperSwitching from systemic steroids to ciclesonide restores the hypothalamic pituitary-adrenal axis - Marczak, Jerzy; Ciebiada, Maciej; Górski, Paweł (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2014)
Introduction: Treatment of difficult asthma with oral corticosteroids (OCS) may suppress the hypothalamic-pituitary-adrenal axis. Aim: In this study we have checked if the substitution of OCS with very high doses of ciclesonide may restore the adrenal function without losing the control of the disease. Material and methods: In 5 patients with difficult, uncontrolled asthma despite treatment with OCS, inhaled and systemic glucocorticosteroids were replaced with very high doses of ciclesonide (1600–2400 µg/day). The symptoms of asthma and the lung function were assessed at baseline and on the 28 th , 56 th and 56 th day of treatment, whereas the levels of cortisol and adrenocorticotropic hormone (ACTH) in the morning were measured at baseline and on the 28 th and the 56 th day of treatment. Results: In all patients, the control of asthma symptoms, measured with Asthma Control Test questionnaire, improved from the mean score of 9.4 to 19.8 in 70 days. In 4 subjects force expiratory volume in 1 s improved gradually through the entire study reaching a mean improvement of 585 ml in 70 days. The ACTH levels were normalized in 3 patients after 28 days of observation and in all patients after 56 days. The cortisol level was normalized in 4 patients after 28 days and in another subject after 56 days of treatment with ciclesonide. Conclusions: Switching from prednisone to very high doses of ciclesonide normalized the hypothalamic-pituitary adrenal axis function and also improved the disease control and the lung function in these 5 patients with difficult asthma.